COMPARATIVE STUDY OF ROOT AND STEM OF BHARANGI (CLERODENDRUM SERRATUM (LINN.) MOON) WITH SPECIAL REFERENCE TO PHARMACOGNOSTIC INVESTIGATIONS - Pansare, *T A; Nesari, T M (International Journal of Ayurveda and Pharma Research, 2016)
Ayurved has a long tradition of using herbal medicines in the maintenance of health and management of diseases. Bharangi [Clerodendrum serratum (Linn.) Moon] is one of drugs of choice used systematically for the treatment of respiratory ailments. According to Ayurved, root of Bharangi should be used in the drug formulations. In a market many a times, instead of root, stem of Bharangi is marketed. There is a lack of evidence of efficacy of Bharangi stem to support its medicinal use. Ideally stem of Bharangi should not be used in place of its root unless it is proved similarly efficient. Identity, purity and quality of the raw drugs are the necessary requirements for preparation of the drug formulation. The success of the system depends on the proper use and availability of genuine raw material. However no scientific reports are available on pharmacognostic studies on the stem of Bharangi. Therefore in the present study macroscopic, microscopic, powdered characteristics investigations on the root and stem of Bharangi were carried out and compared. The study provided diagnostic and differentiating characters for identification of root and stem of Bharangi. The Pharmacognostic standards of stem of Bharangi are developed.